Minimally processed "frog skin" melons under different packaging and edible coatings (Research, Society and Development, 2021)
The use of edible coatings contributes to the conservation of vegetables due to their ability to change the atmosphere, reducing physiological processes such as respiration, cell wall degradation, transpiration and, also, by restricting microbial action, thus preserving the quality of plant products, packaging is also an essential factor in the conservation of minimally processed vegetables. The present work sought to study different conservation alternatives that make it possible to increase the shelf life of minimally processed melons 'Pele de Sapo'. The fruits were minimally processed in cubes, submitted to edible coatings by immersion in calcium chloride, cassava starch, chitosan, yam starch and white sweet potato starch, stored in expanded polystyrene trays covered with polyvinyl chloride film, bioriented polypropylene plastic films were also used, and polyethylene terephthalate packaging, totaling 7 treatments and stored at 3º C and analyzed every 2 days, for 10 days. The experiment was conducted in a completely randomized design in a 7 × 6 factorial scheme, with three replications, totaling 126 experimental units. The coatings and packaging associated with refrigeration preserved the quality and integrity of the fruits during storage, ensuring stability of bioactive compounds such as: chlorophylls, carotenoids and extractable polyphenols. The 2% Chitosan treatments (Trat.2) and the Polyethylene Terephthalate packaging (Trat.6) helped significantly in the maintenance and conservation of minimally processed melons in terms of weight loss and fruit appearance.